Thyroid function and atrial fibrillation: Is there a mediating role for epicardial adipose tissue? - Bos, Daniel (Clin Epidemiol, 2018)
BACKGROUND: The underlying mechanism of the association between thyroid function and atrial fibrillation (AF) is poorly understood, but epicardial adipose tissue (EAT) could be a promising mediator. METHODS: In the 1995 participants (mean age 64.5 years) from the population-based Rotterdam Study, we measured thyroid function (thyroid-stimulating hormone, free thyroxine [FT4]) and performed computed tomography to quantify EAT volumes. All participants were followed for the occurrence of AF. We assessed associations of thyroid-stimulating hormone and FT4 with EAT and AF and performed causal mediation analysis to decompose the overall effect of thyroid function on AF with EAT as mediator. RESULTS: Higher FT4 levels were associated with larger EAT volumes in persons with large waist circumferences, defined by sex-specific cutoffs (0.08 mL more EAT per 1-SD increase in FT4, 95% CI: 0.02, 0.14), but not in persons with a normal waist circumference. In persons with a large waist circumference, higher FT4 levels were associated with a higher AF risk (hazard ratio 1.50, 95% CI: 1.22, 1.83). We found no evidence of a mediating role of EAT in the association of thyroid function with AF (mediated interaction 1.6%, pure indirect effect 3.2%). The estimate of reference interaction of EAT with thyroid function on AF risk was more substantial (10.8%), but statistically nonsignificant. CONCLUSIONS: Higher FT4 levels are associated with larger EAT volumes in persons with abdominal obesity. We report no mediating role of EAT in the association of thyroid function with AF, but found evidence for a suggested interaction of FT4 with EAT volumes on AF risk.